KOPUMPSA receives 350 Best Cooperatives in Malaysia Award - Mohd Raizalhilmy, Mohd Rais (UMPSA, 2025)
KUANTAN, 25 January 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah Cooperative Berhad (KOPUMPSA) proudly ranked among the recipients of the 350 Best Cooperatives in Malaysia Award recently.